PENGENALAN DAN PELATIHAN AUTOCAD UNTUK MENINGKATKAN KOMPETENSI SISWA SMA YAPEMRI DEPOK - FAUZIYA BAGAWAT SARI (KRIDA CENDEKIA, 2024)
AutoCAD is a Computer Aided Drafting and Design (CAD) program used to draw and design in two or three dimensions with a computer. This program is very useful in school learning, enriching the teaching and learning process through interactive and relevant learning in various fields of work, especially design. AutoCAD not only helps in working drawings but also functions as an important communication tool in the world of engineering. Working drawings make it easier for implementers to realize designs into physical forms and must be easy to understand. Field observations show that previous AutoCAD materials tend to be theoretical with limited hardware and human resources. This training aims to improve the knowledge and skills of participants, build strong building drawing engineering competencies to support their careers as planners. The results of community service activities show that partners have increased their understanding of AutoCAD theory and the application of AutoCAD applications to building structures. This is evident from the increase in pre-test and post-test scores, from 36% to 67% after being given an introduction and training on AutoCAD.